Gambaran Karies Gigi Molar Pertama Permanen pada Siswa-Siswi SDN 03 Simpang Utara Kecamatan Simpang Alahan Mati - Mulia Marni; Alhamda, Syukra (CV. CENDIKIA JENIUS INDONESIA, 2024)
Permanent first molars are most susceptible to dental caries after eruption because they have pits and fissures, making them a place for food retention. First molars grow at the age of 6 years. This study aims to determine the frequency distribution of permanent first molar caries based on the age group 7 to 12 years and gender in students at SDN 03 Simpang Utara, Simpang Alahan Mati District. This research uses a quantitative type with a descriptive design. The population in the study were all students of SDN 03 Simpang Utara, Simpang Alahan Mati sub-district, totaling 98 students with a saturated sample by examining the first permanent molars for caries. The data analysis used is univariate analysis. The frequency distribution of permanent first molar caries based on the age group of 7 to 12 years among students is 73% with an average DMFT of 1.74. The age group that experienced the most caries in permanent first molars was children aged 12 years, namely 100% with an average DMFT of 2.87. The gender that most often experiences permanent first molar caries is female, 77% with an average DMFT of 1.78. The conclusion of this study shows that the appearance of caries in the permanent first molar teeth in the majority of students at SDN 03 Simpang Utara has caries in the permanent first molar teeth. It is recommended to all respondents to reduce sweet and sticky foods and maintain better oral and dental health by brushing their teeth twice a day and having dental health checks once every 6 months at a dental health service.